Respuesta :

Answer:

-3 + (n-1)(-4)

Step-by-step explanation:

We follow the formula.

a1 + (n-1)d

d is the common difference.

Answer:

-4n + 1

Step-by-step explanation:

-3, - 7, -11 , -15 ,-19 ,.........

[tex]a_{1} = -3\\\\[/tex]

Common difference (d) = 2nd term - first term

                                  d = -7 -(-3)

                                     = -7 + 3

                                 d = -4

[tex]a_{n} =a + (n-1)d\\\\a_{n} = -3 + (n - 1)(-4)[/tex]

    = -3 + n *(-4) - 1*(-4)

   = -3 - 4n + 4

  = -4n + 1